2018
DOI: 10.1111/micc.12509
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical myocardial dysfunction in coronary slow flow phenomenon: Identification by speckle tracking echocardiography

Abstract: Objective This study aimed to determine whether STE could help detect subclinical myocardial dysfunction in patients with CSFP. Methods Sixty patients with CSFP confirmed by CAG and 51 controls with normal coronary flow were prospectively enrolled. Coronary angiographic data and conventional and speckle tracking echocardiographic parameters of the LV and RV were obtained for every subject. Results Compared with controls, CSFP patients presented with higher BMI and TG levels, but lower HDL‐C levels. Conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…A recent study confirmed that the low serum albumin level at admission is an independent predictive factor for NR following pPCI in STEMI patients [ 29 ]. The coronary slow flow phenomenon is present in patients with lower high-density lipoprotein cholesterol (HDL-C) but higher BMI and TG levels [ 30 ]. An independent study confirmed that the atherogenic index of plasma (logTG/HDL-C) is independently associated with NR [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study confirmed that the low serum albumin level at admission is an independent predictive factor for NR following pPCI in STEMI patients [ 29 ]. The coronary slow flow phenomenon is present in patients with lower high-density lipoprotein cholesterol (HDL-C) but higher BMI and TG levels [ 30 ]. An independent study confirmed that the atherogenic index of plasma (logTG/HDL-C) is independently associated with NR [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Before a diagnosis of coronary slow flow (CSF) can be made, other potential causes must first be excluded. These include medical conditions, such as severe coronary artery stenosis, coronary artery spasm, and gas embolism, as well medical treatments that might produce this phenomenon, including coronary angioplasty and thrombolytic therapy Original Article A preliminary study of MMP-9 and sCD40L in patients with coronary slow flow Xiaobing Zhang 1 , Jiandong Ding 2 , Siliang Xia 1 (5,6). Patients with CSF experience unexplained recurrent chest pain symptoms (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Among 12 studies that measured global longitudinal systolic strain (GLSS) by 2D‐STE in all myocardial segments and full myocardial thickness and/or 3D‐STE without considering the myocardial layer, nine reported declined GLSS values in patients with CSFP 27,29–31,33,35,39–41,43,44,51 . Some studies measured GLSS based on all myocardial layers (endocardial, midmyocardial, and epicardial layers) 32,38,51 .…”
Section: Resultsmentioning
confidence: 99%